2021
DOI: 10.1039/d1dt00658d
|View full text |Cite
|
Sign up to set email alerts
|

Graphitic nitrogen in carbon catalysts is important for the reduction of nitrite as revealed by naturally abundant15N NMR spectroscopy

Abstract: Metal-free nitrogen-doped carbon is considered as a green functional material, but the structural determination of the atomic positions of nitrogen remains challenging. We recently demonstrated that directly-excited solid state 15N...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 82 publications
0
10
0
Order By: Relevance
“…Indeed, among the nuclei relevant for this study, nitrogen is the most challenging one. This is because the NMR active isotope 14 N exhibits severe spectral broadening due to quadrupolar interaction (with exceptions for highly symmetric environments), and the other active isotope 15 N suffers from low natural abundance and, therefore, sensitivity, which often requires isotope enrichment. However, it has been shown that 15 N NMR is capable of delivering crucial information for the nitrogen inserted in materials .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, among the nuclei relevant for this study, nitrogen is the most challenging one. This is because the NMR active isotope 14 N exhibits severe spectral broadening due to quadrupolar interaction (with exceptions for highly symmetric environments), and the other active isotope 15 N suffers from low natural abundance and, therefore, sensitivity, which often requires isotope enrichment. However, it has been shown that 15 N NMR is capable of delivering crucial information for the nitrogen inserted in materials .…”
Section: Introductionmentioning
confidence: 99%
“…These results imply good catalytic stability during the NO 3 RR for the NDC-800 catalyst, which is consistent with previous carbon-based materials studies. 59,73…”
Section: Resultsmentioning
confidence: 99%
“…catalyst, which is consistent with previous carbon-based materials studies. 59,73 To verify the source of ammonia, the electrolyte without NO 3 − was also tested as a control experiment for the electrochemical NO 3 RR. The result showed that the electrochemical NO 3 RR measured in blank Na 2 SO 4 electrolyte yielded a negligible concentration of NH 4 + (Fig.…”
Section: Catalysis Science and Technology Papermentioning
confidence: 99%
See 1 more Smart Citation
“…However, the electrochemical NO 2 − reduction reaction (NO 2 − RR) involves a complex six-electron pathway with various possible by-products (N 2 H 4 , N 2 , and H 2 ), thus requiring highly active catalysts for selective NO 2 − -to-NH 3 conversion. 18–27…”
mentioning
confidence: 99%